Assessment of Helicopter Flyover Noise for Tonal Components (Global Journal of Medical Research, 2020)
Tonal noise is produced by bodies rotating at high speeds such as helicopters. Sounds of the same amplitude will produce different responses depending on the tonal content of the sound. Previous studies suggest that tonal noise is more annoying than broadband noise. Nowadays, sound level meters that can detect tonal noise directly are available in the market, but they are very expensive and beyond the reach of most environmental noise researchers. Hence, the need to adopt an analytical method that can be used to analyze and detect the presence of pure tones in helicopter flyover noise. This paper employs the simplified method suggested by the International Organization for Standardization (ISO). An objective study of the total noise environment in Mgbuoshimini Community Nigeria was carried out to determine the presence of tonal components. Results showed that the total noise environment in the Mgbuoshimini community was mostly characterized by broadband noise, with tonal components detected in four locations (Location 7 at 250 Hz, Location 18 at 6.3 kHz, Location 19 at 6.3 kHz, and Location 20 at 6.3 kHz.
Keywords: tonal noise; broadband noise; international organization for standardization